Work-family enrichment : Sharing Malaysians’ experiences - Hassan, Zaiton; Dollard, Maureen F.; Winefield, Anthony H. (2009)
Work-family enrichment has been receiving increased attention in the Western literature but evidence from Eastern cultures is almost nonexistent. The aim of this study is to highlight enrichment (both work to family and family to work) in the Malaysian work-family context. Respondents to a survey were 506 employees from three public and three private sector organisations in Sarawak, Malaysia. One way ANOVA and Structural Equation Modeling were used to analyse the data. The results showed that, Malaysian respondents reported high work – family enrichment, with the family to work direction (FWE) stronger than the work to family direction (WFE). Both types of enrichment were positively related to the importance of religion and perception of religiousness and differed significantly between ethnic and religious groups. WFE was positively related to job satisfaction, while FWE was positively related to family, community and life satisfaction, suggesting a same domain effect. Aspects of Eastern culture are discussed to explain the findings.